Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1200/jco.1996.14.4.1236
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and pharmacologic study of 9-aminocamptothecin given by 72-hour infusion in adult cancer patients.

Abstract: The recommended phase II dose of 9-AC given by 72-hour infusion every 2 weeks is 35 microg/m2/h without G-CSF or 47 microg/m2/h with G-CSF support. Dose escalation in individual patients may be possible according to their tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…As an S phase-specific drug whose cytotoxicity operates during DNA synthesis, optimal therapeutic efficacy requires prolonged exposure to 9-AC concentrations exceeding a minimum threshold [14]. Due to greater sensitivity of humans (compared to animals) to its myelosuppressive effects, dose-dependent myelosuppression has precluded the use of the 9-AC levels required to achieve plasma concentrations necessary for optimal antitumor activity [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…As an S phase-specific drug whose cytotoxicity operates during DNA synthesis, optimal therapeutic efficacy requires prolonged exposure to 9-AC concentrations exceeding a minimum threshold [14]. Due to greater sensitivity of humans (compared to animals) to its myelosuppressive effects, dose-dependent myelosuppression has precluded the use of the 9-AC levels required to achieve plasma concentrations necessary for optimal antitumor activity [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Leucopenia appeared to be the dose-limiting toxicity, together with modest thrombocytopenia. Nausea and vomiting, alopecia, stomatitis and diarrhoea were less frequently reported (Rubin et al, 1994;Takimoto et al, 1994;Dahut et al, 1996). Steady-state plasma concentrations increased linearly with the dose and ranged from 0.9 to 10.6 nm and correlated well with percentage decrease of granulocyte count (Takimoto et al, 1994).…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…The amino substitution at the 9 position of the A ring improves solubility of the drug, and the drug has activity against many solid tumor cell lines in athymic animals [7,8]. Phase 1 trials of 9-AC have suggested potential efficacy of the agent against brain tumors [3,9,10]. One previous trial showed a lack of efficacy of 9-AC against newly diagnosed GBM and recurrent high-grade glioma although that trial was not complete at the time this study was initiated [11].…”
Section: Introductionmentioning
confidence: 99%